24-hour intraocular pressure fluctuation monitoring using an ocular telemetry Sensor: tolerability and functionality in healthy subjects - De Smedt, Stefan; Mermoud, André; Schnyder, Corinne (Journal of glaucoma, 2012)
To evaluate the tolerability, comfort, and reliability of the signal transmission of an ocular Sensor used for 24-hour intraocular pressure fluctuation monitoring in humans. In this uncontrolled open trial involving 10 healthy volunteers, an 8.7-mm radius prototype ocular telemetry Sensor (SENSIMED Triggerfish, Lausanne, Switzerland) and an orbital bandage containing a loop antenna were applied and connected to a portable recorder after full eye examination. Best-corrected visual acuity and position, surface wetting ability, and mobility of the Sensor were assessed after 5 and 30 minutes, 4, 12, and 24 hours. Subjective wearing comfort was scored and activities documented in a logbook. After Sensor removal, a full eye examination was repeated and the recorded signal analyzed. The comfort score was high and did not fluctuate significantly over time. The mobility of the Sensor was limited across follow-up visits and its surface wetting ability remained good. Best-corrected visual acuity was significantly reduced during Sensor wear and immediately after its removal (from 1.07 before, to 0.85 after, P value 0.008). Three subjects developed a mild, transient corneal abrasion. In all but 1 participant, we obtained usable data of a telemetric signal recording with sufficient sensitivity to depict ocular pulsation. This 24-hour trial has encouraging results on the tolerability and functionality of the ocular telemetric Sensor for intraocular pressure fluctuation monitoring. Further studies with different Sensor radii conducted on a larger study population are needed to improve comfort, precision, and interpretation of the telemetric signal.